Can friends protect genetically vulnerable children from depression?. (30th April 2013) - Brendgen, Mara; Vitaro, Frank; Bukowski, William M.; Dionne, Ginette; Tremblay, Richard E.; Boivin, Michel
Abstract: The study examined whether reciprocal friendship quantity or quality can mitigate genetic vulnerability for depression symptoms in children. The sample comprised 168 monozygotic twin pairs and 126 same-sex dizygotic twin pairs assessed in Grade 4 (mean age = 10.04 years). Friendship participation was measured via reciprocal nominations of close friendships within the classroom. Friendship quality was measured through self-reports. Depression symptoms were measured through teacher and peer reports. Genetic vulnerability for depression symptoms was unrelated to friendship participation or the number of reciprocal friends, but it was negatively related to positive friendship quality. In line with gene–environment interaction, genetic risk effects on depression symptoms were mitigated in girls who had at least one close reciprocal friend. In boys, only moderate main effects of genetic vulnerability and friendship participation were found but no interaction between them. However, among boys with at least one reciprocal friend, a greater number of friends was related to fewer depression symptoms whereas no cumulative effect of friendship was found for girls. Finally, positive friendship quality was related to fewer depression symptoms in girls and boys even when controlling for genetic risk. The findings emphasize the importance of teaching social interactional skills that promote high-quality friendship relations to help prevent the development of depression symptoms in children.